Educational theater in promoting conscious use of digital technologies among children: Experience and impacts (Research, Society and Development, 2024)
This article aimed to describe and share the experience of developing and applying an intervention designed by medical students, which used theater as a tool to promote the balanced use of digital technologies among children. The methodology adopted was descriptive and narrative, focusing on experience reports, aiming to detail and share observations and practices experienced during the research. The play addressed the behavioral and emotional consequences of excessive screen use, encouraging children to adopt healthier habits. The participation of medical students provided an enriching practical experience, developing communication and interaction skills. This study highlights the importance of active teaching methodologies in the training of health professionals and the contributions of theater as an educational tool in promoting child health.